2012
DOI: 10.1016/j.bandc.2011.10.011
|View full text |Cite
|
Sign up to set email alerts
|

Recollection training and transfer effects in Alzheimer’s disease: Effectiveness of the repetition-lag procedure

Abstract: Effectiveness of the repetition-lag procedure in Alzheimer's disease is discussed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
54
2
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(60 citation statements)
references
References 56 publications
3
54
2
1
Order By: Relevance
“…Another limitation is that an active control group was not employed, meaning that the results could be due to factors such as experimenter contact. This latter concern is ameliorated by the finding that previous research with active control groups using RLT have found that recognition practice with an equivalent amount of contact time does not produce the same training or transfer gains as RLT (Boller et al, 2012).…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…Another limitation is that an active control group was not employed, meaning that the results could be due to factors such as experimenter contact. This latter concern is ameliorated by the finding that previous research with active control groups using RLT have found that recognition practice with an equivalent amount of contact time does not produce the same training or transfer gains as RLT (Boller et al, 2012).…”
Section: Discussionmentioning
confidence: 97%
“…In another study using a modified form of RLT (Lustig & Flegal, 2008) gains were found on Trails B (cognitive flexibility) along with a reduction in selfreported memory errors as measured by the Everyday Memory Questionnaire. In a group with Alzheimer's disease (Boller, Jennings, Dieudonné, Verny, & Ergis, 2012) transfer gains were seen on an n-back task (working memory), RL/R1 (episodic recognition memory), DMS 48 task (visual recognition memory), and the source recognition task (recognition memory). One conference report found gains in a group with aMCI on the California Verbal Learning Test -Second Edition (CVLT-II) measures of immediate and delayed, free and cued recall (Jennings et al, 2006).…”
Section: Transfer Of Trainingmentioning
confidence: 99%
“…Although aged rodents show deficits in performing spatial memory tasks, they are eventually able to perform more like young animals with continued training (Figure 2; Magnusson et al, 2010). This procedure has even benefited individuals suffering from Alzheimer's disease (Boller et al, 2012). In addition, repetition, using techniques like repetition-lag training, improves the acquisition of new material in older individuals.…”
Section: Benefits Of Practicementioning
confidence: 99%
“…The behavioral intervention approaches available include, among others, (a) reality orientation training and memory exercises to promote the persons' cognitive and interactive functioning within their context (Boller, Jennings, Dieudonné, Verny, & Ergis, 2012;Cotelli, Manenti, Zanetti, & Miniussi, 2012;Zanetti et al, 2001), (b) technology-aided instructions to help the persons carry out multi-step (functional) daily activities and self-care routines (Lancioni et al, 2012;Lancioni et al, 2014;Perilli et al, 2013), (c) dance and psychomotor activation to improve the persons' cognitive and social behavior (Guzmán-García, Mukaetova-Ladinska, & James, 2013;Hopman-Rock, 2000;Hopman-Rock, Staats, Tak, & Dröes, 1999), (d) music therapy to reduce the persons' agitation and wandering (Fitzgerald-Cloutier, 1993;Janata, 2012), and (e) technology-aided stimulation and prompts to foster the persons' engagement in mild physical exercise (e.g., arm raising; Lancioni et al, 2015).…”
Section: Introductionmentioning
confidence: 99%